Modeling technology and profitability as moderators of competition, efficiency, and risk in Islamic bank stability - Oktaviana, Ulfi Kartika; Miranti, Titis (Journal of Islamic Economics Lariba, 2025)
IntroductionIslamic commercial banks in Southeast Asia are facing growing challenges as competition intensifies and digital transformation accelerates. Stability has become a central concern, particularly in Indonesia and Malaysia where Islamic finance holds significant market share. While prior studies highlight competition, efficiency, credit risk, and liquidity risk as determinants of financial stability, the moderating influence of technology adoption and profitability has been less explored.ObjectivesThis study investigates the effects of competition, efficiency, credit risk, and liquidity risk on the stability of Islamic commercial banks in Indonesia and Malaysia. It further examines how technology and profitability moderate these relationships, offering a comprehensive understanding of their role in shaping bank resilience.MethodThe research employed a quantitative approach using panel data from 14 Islamic commercial banks between 2010 and 2022. Bank stability was measured with the Z-Score, competition with the Lerner Index, efficiency with operating costs, and credit and liquidity risks with respective ratios. Technology was proxied by non-interest expenditures, while profitability was measured by return on assets. The analysis applied the generalized method of moments to address endogeneity and ensure robust estimates.ResultsThe findings reveal that competition enhances bank stability, while credit and liquidity risks undermine it. Efficiency does not significantly affect stability. Technology exerts a dual effect: it improves stability directly but weakens the stabilizing influence of competition and heightens vulnerabilities linked to liquidity risk. Similarly, profitability supports stability under moderate risk-taking but magnifies the negative effects of excessive credit and liquidity risks. Bank size strengthens stability, whereas bank age is associated with greater fragility.ImplicationsThese results highlight that technology and profitability are double-edged factors: they can either reinforce or erode financial stability depending on how banks align them with risk management practices. Regulators and managers must ensure that digitalization and profit strategies are embedded within disciplined governance frameworks to prevent systemic vulnerabilities.Originality/NoveltyThis study contributes to the Islamic banking literature by introducing technology and profitability as moderators in the stability model, using a cross-country dataset and advanced estimation techniques. It offers new insights for policymakers and practitioners on balancing growth, digitalization, and risk control in sustaining the resilience of Islamic commercial banks.